Association between clinical risk factors and left ventricular function in patients with breast cancer following chemotherapy. (25th November 2020) - Yamashita, K; Tanaka, H; Hatazawa, K; Tanaka, Y; Sumimoto, K; Shono, A; Suzuki, M; Yokota, S; Suto, M; Mukai, J; Takada, H; Matsumoto, K; et al.
Abstract: Background: The sequential or concurrent use of two different types of agents such as anthracyclines and trastuzumab may increase myocardial injury and cancer therapeutics-related cardiac dysfunction (CTRCD), which is often the result of the combined detrimental effect of the two therapies for breast cancer patients. For risk stratification to detect the development of CTRCD, the current position paper from the European Society of Cardiology (ESC) lists several factors associated with risk of cardiotoxicity following treatment with chemotherapy. However, the association between clinical risk factors and left ventricular (LV) function in breast cancer patients is currently unclear. Purpose: Our purpose was to investigate the impact of baseline risk factors on LV function in patients with preserved LV ejection fraction (LVEF) who have undergone anthracycline or trastuzumab chemotherapy for breast cancer. Methods: We studied 86 breast cancer patients treated with anthracyclines, trastuzumab, or both. Mean age was 59±13 years and LVEF was 67±5%. In accordance with the current definition, CTRCD was defined as a decline in LVEF of >10% to an absolute value of <53% after chemotherapy. Based on the 2016 ESC position paper, clinical risk factors for CTRCD were defined as: (1) a cumulative total doxorubicin dose of ≥240 mg/m 2, (2) age ≥65-year-old, (3) body mass index ≥30 kg/m 2, (4) a previous history of radiation therapy to chest or mediastinum, (5) B-type natriuretic peptide ≥100pg/mL, (6) a previous history of cardiovascular disease, (7) atrial fibrillation, (8) hypertension, (9) diabetes mellitus, (10) current or ex-smoker. Results: The relative decrease in LVEF after chemotherapy for patients with more than four risk factors was significantly greater than that for patients without (−9.3±10.8% vs. −2.2±10.2%; p=0.02). However, this finding did not apply to patients with more than one, two or three risk factors. Patients with more than four risk factors also tended to show a higher prevalence of CTRCD than those without (14.3% vs. 2.8%, p=0.12). Moreover, patients with more than four risk factors were more likely to have higher LV mass index (109.3±29.0 g/m 2 vs. 83.2±21.0g /m 2, p<0.001), lower global longitudinal strain (18.4±2.8% vs. 20.0±2.6%, p=0.06) and higher E/e' (10.4 (8.9–13.0) vs. 9.0 (7.4–10.9), p=0.06) compared to those without. Conclusions: Association between clinical risk factors and LV dysfunction following chemotherapy became stronger with an increase in the number of risk factors in breast cancer patients, and was especially strong for patients treated with chemotherapy who had more than four risk factors. Our findings can thus be expected to have clinical implications for better management of patients with breast cancer referred for chemotherapy. Funding Acknowledgement: Type of funding source: None